The impact of dietary factors on the function of brown and beige adipose tissues—implications on health and disease - Bombassaro, Bruna; Batitucci, Gabriela; Reymond Simoes, Marcela; Araujo, Eliana P.; Velloso, Licio A. (Frontiers in Nutrition, 2025)
The development of strategies that promote the activation of adaptive thermogenesis in brown and beige adipose tissues is expected to lead to advances in the prevention and treatment of obesity, diabetes, and cardiovascular diseases. Currently, there is a great effort to identify or develop pharmacological agents that could promote adaptive thermogenesis. However, the greatest candidates, the β3-adrenergic receptor agonists, have proven troublesome as they promote unwanted cardiovascular effects. An important advance in the field of adaptive thermogenesis was made by the identification of nutrients or nutrient-derived substances that activate thermogenesis in brown and beige adipose tissue. The detailed characterization of the mechanisms by which nutrients activate thermogenesis could lead to changes in the nutritional guidelines for metabolic diseases. In addition, these studies could unveil new targets for the development of pharmacological strategies to treat metabolic and cardiovascular diseases. In this article, we review the data that led to the current understanding of the actions of nutrients or nutrient-derived substances as thermogenic agents.